Effects of Twin-Screw Extruders Condition to Physical Properties of Floating Fish Feed - Arif Rahman Hakim; Wahyu Tri Handoyo; Toni Dwi Novianto; Andrianto Widi Prasetyo (Universitas Gadjah Mada, 2019)
Process production of floating fish feed in a society constrained by processing technology. The objective of this study was to observe effect of condition process of twin screw extruders to the physical and chemical properties of produced of floating fish feed. Ingredients used involve fish meal, soybean meal, corn meal, and tapioca flour. The ingredients are mixed with 15, 20 and 25% water added to the total weight. Extrusion process condition conducted by several treatments i.e screw speed (540, 540, 600, 660 rpm) and barrel temperatures (80, 90, 100, 110, 120℃). In order to study, expansion ratio, unit density, floatability and hardness of feed were observed as physical parameters while chemical properties include moisture and protein content. Experimental result showed that addition 25 % water to the formula gives a good performance of expansion ratio, unit density and floatability than 15% and 20% moisture content. Higher of screw speed produces feed with higher ratio expansion, lower unit density, and higher floatability. The optimum of screw speed is 600 rpm. Meanwhile increasing of barrel temperature caused reduction of unit density, and escalation floatability of feed. Best barrel temperature to meet the physical properties is 120℃. The produced feed contain protein 32.38-41.95% and moisture content 4.37-5.70%.